Application of cleaner production strategy for reducing carbon footprint in a healthcare products manufacturing premise / Suhaseni Chelathurai - Suhaseni, Chelathurai (2018)
A Healthcare product manufacturing premise was chosen to study the Cleaner Production (CP) strategy that aims to reduce the CO2 emission from the manufacturing activities. CP audit was conducted to quantify the resources consumption, energy usage, raw material usage and waste. The audit confirms that the carbon emission of a product is 323 kg CO2 / 1000 litre of healthcare product which mainly contributed by 74% electricity and 25% fuel consumption. Besides that, the remaining 1% is contributed by solid waste, water, and waste water. In this study, 31 Cleaner production options were identified to reduce the carbon footprint. The analyses confirm that the identified CP strategy could reduce carbon footprint about 38 kg CO2 / 1000 litre of healthcare products with the strategies focused mainly on the design changes, improved operational, good housekeeping. This is equivalent for reducing 912 ton CO2 /year for this premise. The estimated investment required for this reduction was RM 1.6 million with the payback period of 2 years. Therefore, the CP strategies were the beneficial options to reduce CO2 emission and useful tool for a growing healthcare manufacturing industry.